A novel homozygous SLC39A14 variant in an infant with hypermanganesemia and a review of the literature - Meijiao Zhang; Liping Zhu; Huiping Wang; Ying Hao; Qingping Zhang; Chunyan Zhao; Xinhua Bao (Frontiers Media S.A., 2023)
BackgroundManganese (Mn) is an essential trace metal necessary for good health; however, excessive amounts in the body are neurotoxic. To date, three genes (SLC30A10, SLC39A8, and SLC39A14) have been discovered to cause inborn errors in Mn metabolism in humans. As very rare diseases, the clinical features require further clarification.MethodsA male Chinese patient who mainly presented with hypermanganesemia and progressive parkinsonism-dystonia was recruited for this study. We collected and analyzed clinical information, performed whole-exome sequencing (WES), and reviewed the relevant literature.ResultsThe motor-developmental milestones of the patient were delayed at the age of 4 months, followed by rapidly progressive dystonia. The patient displayed elevated Mn concentrations in blood and urine, and brain magnetic resonance imaging (MRI) showed symmetrical hyperintensity on T1-weighted images and hypointensity on T2-weighted images in multiple regions. A novel homozygous variant of the SLC39A14 gene (c.1058T > G, p.L353R) was identified. The patient was treated with disodium calcium edetate chelation (Na2CaEDTA). Three months later, mild improvement in clinical manifestation, blood Mn levels, and brain MRI was observed. To date, 15 patients from 10 families have been reported with homozygous mutations of SLC39A14, with a mean age of onset of 14.9 months. The common initial symptom is motor regression or developmental milestone delay, with a disease course for nearly all patients involving development of progressive generalized dystonia and loss of ambulation before treatment. Additionally, hypermanganesemia manifests as Mn values ranging from 4- to 25-fold higher than normal baseline levels, along with brain MRI results similar to those observed in the recruited patient. Nine SLC39A14 variants have been identified. Seven patients have been treated with Na2CaEDTA, and only one patient achieved obvious clinical improvement.ConclusionWe identified a novel SLC39A14 mutation related to autosomal recessive hypermanganesemia with dystonia-2, which is a very rare disease. Patients present motor regression or delay of developmental milestones and develop progressive generalized dystonia. Chelation therapy with Na2CaEDTA appears to effectively chelate Mn and increase urinary Mn excretion in some cases; however, clinical response varies. The outcome of the disease was unsatisfactory. This study expands the genetic spectrum of this disease.